OCT4 induces EMT and promotes ovarian cancer progression by regulating the PI3K/AKT/mTOR pathway - Xie, Weiwei; Yu, Jun; Yin, Yujia; Zhang, Xiaoqian; Zheng, Xiaocui; Wang, Xipeng (Frontiers in Oncology, 2022)
Background Octamer-binding transcription factor 4 (OCT4) is a key stem cell transcription factor involved in the development of various cancers. The role of OCT4 in ovarian cancer (OC) progression and its molecular mechanism are not fully understood. Methods First, immunohistochemistry (IHC) assays of ovarian benign cyst tissues, OC tissues, and omental metastatic tissues were performed to reveal OCT4 expression profiles. We knocked down OCT4 in two OC cell lines (SKOV3 and A2780) using a lentiviral vector and performed in vitro and in vivo experiments. OCT4 was knocked down to assess the proliferation, migration, and invasion of OC cells using CCK-8, colony formation, wound healing, and Transwell assays. In addition, the nude tumor mouse model was used for in vivo study. Mechanistically, we demonstrated that OCT4 influenced protein expression in the phosphoinositol 3-kinase (PI3K)/AKT/mTOR pathway and epithelial-mesenchymal transition (EMT)-related proteins by Western blotting and immunofluorescence (IF) assays. The interaction between OCT4 and p-AKT was further confirmed by coimmunoprecipitation (CoIP) assays. Importantly, AKT activation by its activator SC79 reversed the biological functions of OCT4 knockdown. Results OCT4 expression was significantly upregulated in OC samples and metastatic tissues. OCT4 knockdown notably inhibited the proliferation, migration, and invasion of OC cells in vitro and in vivo. Moreover, the expression of p-PI3K, p-AKT, and p-mTOR was downregulated after OCT4 knockdown. An AKT agonist reversed the effect of OCT4 knockdown on OC cells. EMT in OC samples was enhanced by OCT4. Conclusions Our study shows that OCT4 promotes the proliferation, migration, and invasion of OC cells by participating in the PI3K/AKT/mTOR signaling axis, suggesting that it could serve as a potential therapeutic target for OC patients.